APPLICATIONS OF QUECHERS TECHNIQUE FOR DRUG EXTRACTION FROM POSTMORTEM SAMPLES IN A MEDICO LEGAL SETTING - Kachhawaha, Akanksha Singh; Rajan, Athulya; Anand, Akhi; Johnson, Abraham (Journal of Forensic Medicine and Toxicology, 2024)
QuEChERS, that stands for Quick, Easy, Cheap, Effective, Rugged, and Safe, is a sample preparation technique commonly used in analytical chemistry, forensic medicine and toxicology. This method is primarily employed for the extraction and cleanup of complex samples, such as biological tissues or fluids, to prepare them for analysis by techniques like chromatography and mass spectrometry. QuEChERS is particularly useful for the analysis of pesticides, drugs, and other contaminants. The QuEChERS technique is preferred for its simplicity, speed, and cost-effectiveness. It has recently found widespread use in various fields, especially in forensic medicine and toxicology, wherein the detection and analysis of complex matrices for drugs, poisons, or contaminants is essential for investigations and legal proceedings.
Keywords: QuEChERS; Extraction; Viscera; Postmortem samples; Medico-legal